AN ALTERNATIVE CONCEPT OF FUZZY FUNCTIONAL DEPENDENCY BY USING CONDITIONAL PROBABILITY - Intan, Rolly (Institute of Research and Community Outreach - Petra Christian University, 2001)
This paper proposes an alternative concept of Fuzzy Functional Dependency (FFD) based on the theory of conditional probability. We examine some properties of conditional probability and its relation with fuzzy sets. Moreover, approximate conditional probability of two fuzzy sets can be considered to determine the degree of similarity between two fuzzy sets. Based on this property, we propose an alternative concept of FFD and prove that it satisfies classical/crisp relational database. Abstract in Bahasa Indonesia : Sebuah alternatif konsep dari Fuzzy Functional Dependency (FFD) berdasarkan teori conditional probability diperkenalkan beberapa properties dan conditional probability dalam hubungannya dengan fuzzy sets didiskusikan. Conditional probability dan dua fuzzy sets dipertimbangkan untuk menentukan derajat kesamaan dan dua fuzzy sets. Berdasarkan konsep ini ini, diperkenalkan sebuah alternatif konsep dari FFD. Kata kunci: fuzzy sets, fuzzy functional dependency, fuzzy relational database, conditional probability.